Aviation maintenance technician handbook. Volume 1, volume 2. (U.S. Department of Transportation, Federal Aviation Administration, Airman Testing Standards Branch, 2018)
Designed for use by instructors and applicants preparing for the FAA Knowledge Exam and Oral & Practical (O & P) Exams required for obtaining an Aviation Maintenance Technician (AMT) certificate with Airframe or Powerplant rating or both (also called an A & P license). This Powerplant (Volumes 1 and 2) provides the basic information on principles, fundamentals, and technical procedures in the subject matter areas relating to the powerplant rating including: Aircraft Engines, Engine Fuel and Fuel Metering Systems, Induction and Exhaust Systems, Engine Ignition and Electrical systems, Engine Starting Systems, Lubrication and Cooling Systems, Propellers, Engine Removal and Replacement, Engine Fire Protection Systems, Engine Maintenance and Operation, Light-Sport Aircraft Engines. These 2018 editions reflect current techologies, equipment and procedures. Illustrated throughout with detailed, full-color drawings and photographs, with a comprehensive glossary and index.